Analisis Pengaruh Jumlah Uang Beredar (Jub), Kurs dan Suku Bunga Terhadap Laju Inflasi Di Indonesiatahun 1999-2014 - Komariyah, Astutik, Eni Setyowati, SE, M.Si (2016)
Inflation is one of the many economic problems get the attention of economic thinkers. One of the macro-economic indicators that are used to see or measure the stability of a country's economy is inflation. Changes in these indicators will impact on the dynamics of economic growth. The turmoil partly because the inflation factor. Pelitian The purpose of this is to analyze how the influence of money supply (JUB), EXCHANGE and the interest rate to the inflation rate in Indonesia. The analytical method used in this research is using multiple linear regression analysis method (OLS). The results of this study indicate that EXCHANGE positive and significant effect on the rate of inflation and the money supply and interest rates had no significant effect on the rate of inflation in Indonesia.